‘VL Bhat 201’ soybean a high-yielding nutrition rich black variety - Bhartiya, Anuradha; Pal, R S; Singh, Sher; Kant, L (Indian Farming, 2018)
Black soybean (Bhat) is an major traditional legume of Uttarakhand hills which fondly consumed as pulse in contrary to oilseed yellow soybean. It plays a vital role in the nutritional and livelihood security of resource poor rural and tribal population of the region and accounts a sizable acreage in this region but stagnant productivity levels has resulted into unprofitability in cultivation and great neglectance of this valuable crop. Recently released variety of black soybean ‘VL Bhat 201’ is promising in its yield potential (1,642 kg/ha) as compared to traditional poor plant type and low yielding cultivars as well as it has high innate resistance against prevalent diseases and insect pest of black soybean in hills besides, excellent nutritional quality. Furthermore, secondary agriculture and utilization of this legume as nutraceutical/ functional food is need be encouraged to realise its real commercial potential for income generation in the region.